Edukasi dan Pemeriksaan Kadar Asam Urat (Gout) pada Masyarakat di Kecamatan Gedong Tataan, Provinsi Lampung - Annisa Primadiamanti; Selli Marselena M; Putri Nanda Tiarani; Tarisa Saputri; Sella Saputri; Syifa Nurul Afifa (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Uric acid disease (gout) remains a prevalent metabolic health issue, particularly among adults and the elderly. Low awareness of early detection and limited knowledge regarding risk factors are major obstacles to preventing complications. This community service activity aimed to improve public understanding and conduct early screening of uric acid levels in Gedong Tataan District, Lampung Province. The implementation methods included health education through interactive lectures and discussions, digital uric acid testing, and knowledge evaluation using pre-test and post-test instruments. Fifty participants attended the activity, predominantly aged 51–60 years. The results showed a significant increase in knowledge, with the average score rising from 35.6 in the pre-test to 88.3 in the post-test (p-value = 0.00). The screening identified several residents with uric acid levels above the normal threshold. This activity proved effective as a promotive and preventive effort to encourage healthy lifestyle changes and increase community awareness regarding the importance of routine health monitoring to prevent gout complications.